Simulation and optimization of low pressure casting process forAlSi9Mg gearbox shell - Futao WU (Hebei University of Science and Technology, 2021)
In order to solve the problems of porosity,slag inclusion,shrinkage porosity,etc.,the influence of low pressure casting process parameters on filling and solidification of the AlSi9Mg gearbox shell was studied.Two different gating systems of the three-dimensional solid model were drawn with Pro/Engineer software,and the influence of pouring temperature,mold temperature and filling pressure on the alloy filling and solidification process during low pressure casting of the AlSi9Mg gearbox shell were studied through the method of numerical simulation using ProCAST software.Based on the experimental results,effective analysis was conducted with orthogonal test table.The result shows that the reasonable process parameters are as follows:Pouring temperature 700 ℃,mold temperature 350 ℃ and filling pressure 45 kPa,and under these process parameters,the defect volume of shrinkage pore of the casting is reduced from 1[KG-*4]537 cm3 to 1[KG-*4]425 cm3.The research on simulation and optimization of low-pressure casting process of AlSi9Mg gearbox lower shell can provide reference for optimization of low-pressure casting process of gearbox lower shell,and has practical application value.